FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA MEMILIH PRODI PKK JURUSAN ILMU KESEJAHTERAAN KELUARGA FAKULTAS PARIWISATA DAN PERHOTELAN UNIVERSITAS NEGERI PADANG - Rahmawati, Dewi; Ernawati, Ernawati; Nelmira, Weni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This study aimed to describe the interest of students, the intrinsic factor(aptitude and motivation), extrinsic factors (the role of parents and peers),determine the influence of factors of intrinsic and extrinsic factors in choosing theStudy Program of Family Welfare (Prodi PKK) Department of IKK FPP UNP.The research type is quantitative descriptive research. The population of thisresearch is students of PKK Study Program of FPP UNP Class of 2012-2016registered in semester of January-June 2017 as many as 211 people. Samplingtechnique using Stratified Random Sampling technique with a sample of 68people. Data collection with questionnaires using Likert scale and analyzed byregression. The results showed the interest of students in the high category(79.65%), the intrinsic factor (aptitude and motivation) high category (80.56%)where talent is very high category (85.18%) and motivation high category(74.22%). Extrinsic factors (the role of parents and peers) very high category(81.32%), where the indicator role of parents is very high category (88.26%) andpeer high category (74.38). Based on the F test the intrinsic factors (talent andmotivation) and extrinsic factors (the role of parents and peers) give effect of33.1%. Persisally (t test) intrinsic factor (talent and motivation) influenced studentinterest 27,7% with 25% talent and motivation 9.4%. Extrinsic factors (the role ofparents and peers) affect student interest 19.5% with details of the role of parents13.9% and peers 11.8%. So the biggest factor influencing the student's interest inchoosing the PKK Study Program of IKK FPP UNP is the intrinsic factor of talentand motivation.Keywords: Talent, motivation, parent's role, peers, Interests